2018
DOI: 10.1038/protex.2018.022
|View full text |Cite
|
Sign up to set email alerts
|

therascreenPITX2 RGQ PCR assay for the assessment of PITX2 DNA-methylation status to investigate the role of the transcription factor PITX2 and the regulation of the Wnt/ß-catenin pathway in pathophysiological processes.

Abstract: The therascreen PITX2 RGQ PCR assay is an optimized in vitro DNA methylation-specific quantitative real-time PCR test intended for the determination of the percent methylation ratio (PMR) in the pituitary homeobox 2 (PITX2) transcription factor gene promoter 2. The test uses bisulfite-converted genomic DNA derived from formalin-fixed paraffin-embedded tumor tissues of breast cancer patients. The PMR will aid clinicians in selecting adjuvant systemic chemotherapy, e.g. anthracycline-based chemotherapy in high-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The present retrospective study was conducted by applying a fully analytically validated quantitative methylation-specific real-time PCR format [16] and an optimized clinically validated cut-off to extend previously published studies. Hartmann et al [10] investigated the value of PITX2 DNA methylation in 241 lymph node-positive, ER-positive and HER2-negative breast cancer patients, a patient cohort with the same clinicopathological characteristics as the present study, and showed the significant role of PITX2 DNA methylation in the prediction of outcome after adjuvant anthracycline treatment, at that time by applying a microarray-based test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present retrospective study was conducted by applying a fully analytically validated quantitative methylation-specific real-time PCR format [16] and an optimized clinically validated cut-off to extend previously published studies. Hartmann et al [10] investigated the value of PITX2 DNA methylation in 241 lymph node-positive, ER-positive and HER2-negative breast cancer patients, a patient cohort with the same clinicopathological characteristics as the present study, and showed the significant role of PITX2 DNA methylation in the prediction of outcome after adjuvant anthracycline treatment, at that time by applying a microarray-based test.…”
Section: Discussionmentioning
confidence: 99%
“…After bisulfite conversion with the Epitect Fast DNA Bisulfite Kit (QIAGEN, Hilden, Germany), the PMR of 3 CpG motifs of the PITX2 gene P2 [11] was quantified by qMSP using the therascreen PITX2 RGQ PCR kit, containing the quantitative PCR (qPCR) reaction mix, primer and probes as well as positive and negative controls. The assay was performed on the Rotor-Gene Q MDx real-time PCR platform (QIAGEN, Hilden, Germany) and automatically assessed by the Rotor-Gene AssayManager® software V2.1 with installed Gamma Plug-in and PITX2 -specific assay profile (therascreen_PITX2_FFPE_CE Assay Profile v1.0) for data analysis and quality control [16]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Therascreen PITX2 RGQ PCR assay , developed by Perkins et al (2018) in conjunction with the Therawis Diagnostics Company, analyzes the methylation status of the PITX2 gene obtained from the DNA of FFPE biospecimens. PITX2 methylation is assessed by methylation-specific real-time PCR and exploits the quantitative PCR (qPCR) oligonucleotide hydrolysis principle of two TaqMan probes labeled with different fluorescent dies (FAM ™ for fully methylated and HEX ™ for fully unmethylated DNA) in combination with methylation nonspecific primers to measure the methylation status of the target sequences of PITX2 gene promoter 2 in bisulfite-treated DNA.…”
Section: In Vitro Diagnostic Tests Based On Epigenetic Biomarkersmentioning
confidence: 99%
“…The Therascreeen PITX2 RGQ PCR assay can be easily adopted in clinical laboratories that already run other Therascreen assays commercialized by Qiagen. The complete workflow is streamlined throughput for a medium sample with highly reliable and robust readouts and can be performed in a time of 2 working days (Perkins et al, 2018).…”
Section: In Vitro Diagnostic Tests Based On Epigenetic Biomarkersmentioning
confidence: 99%